False-Positive Tuberculin Skin Test Results Among Low-Risk Healthcare Workers Following Implementation of Fifty-Dose Vials of Purified Protein Derivative. (2nd April 2018) - Collins, Jeffrey M.; Hunter, Mary; Gordon, Wanda; Kempker, Russell R.; Blumberg, Henry M.; Ray, Susan M.
Abstract : Following large declines in tuberculosis transmission the United States, large-scale screening programs targeting low-risk healthcare workers are increasingly a source of false-positive results. We report a large cluster of presumed false-positive tuberculin skin test results in healthcare workers following a change to 50-dose vials of Tubersol tuberculin. Infect Control Hosp Epidemiol 2018;39:750–752